Adaptation of the Javanese Transmigration Community Towards Jambi Culture in Wanareja Rimbo Ulu Tebo Village 1978-1990 - Karuniasari, Sara; Kurniawanti, Merci Robbi; Purnomo, Budi (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The aim of writing this article is to know: (1) the beginning of transmigration in Wanareja Village (2) efforts to adapt the Javanese transmigration community to Jambi Culture, (3) the factors inhibiting and driving the adaptation of the Javanese transmigration community in Wanareja Village, and (4) the contribution of the community Javanese transmigration of Jambi Culture in 1978-1990. This research uses a historical research method which consists of 4 stages, namely heuristics, source criticism, interpretation, and historiography. The results of this research are: (1) transmigration in Wanareja Village occurred in several waves. Firstly, in June-October 1978 was filled with Magelang’s and Semarang’s people, secondly in 1979 was filled with Brebes’s People. (2) the efforts of the Javanese people to adapt the Jambi’s Culture, including through communication, achieving goals, integration and latency, (3) the driving factor is limitations in speaking Indonesian and the supporting factor are friendly and flexible attitude by the Javanese transmigration community, (4) the contribution of the Javanese transmigration community are in the religious system is acculturation of the berzanji tradition with Malay rhythms, the knowledge system introducing Weton counting, social organizations forming Karang Taruna, and the living equipment system recognizing the rice planting tool, namely Unjung.